Study of Arthropod Diversity in the Location of Pine Forests and Orange Groves in the Bedengan Campground Area, Malang Regency - Naim, Abu; Swandayani, Rosalina Edy; Pribadi, Titanio Auditya (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
The Bedengan campground is a location with natural conditions that are still natural which is dominated by pine forests. Around the forest, there are orange plantations managed by the local community. To determine the comparison of Arthropod diversity in the two locations, the Pitfall trap, Net, and Barrel turgin methods were used with data analysis using Shannon-Wiener and QBS index. Based on the results of the research that has been carried out, it can be seen that there are 11 orders, 29 families and 487 species, while in the orange plantation area there are 7 orders, 10 families and 335 species. In addition, based on the calculation of the Diversity Index (H') and the QBS Index in both areas, there is a significant difference. Pine areas have a higher diversity index value compared to orange plantation areas. High Important Value Index (INP) includes the family Myrmicidae, family Entomobridae, and Cicadelidae, the three arthropod families are types of arthropods that have behaviors that are easily adapted to the environment. Environmental quality has a significant difference in the relatively stable and low pine area, while in the orange plantation area it has a quality that tends to be dry. According to the QBS analysis on the citrus plantation area, the quality of arthropods and environmental biotics is influenced by the use of peptideicides that have an impact on soil diversity and mesofauna Keywords: Bedengan campground, Arthropods, index Shannon-Wiener dan index QBS